STRATEGIC MANAGEMENT OF SMART-CITY DEVELOPMENT IN UKRAINE IN THE POST-WAR PERIOD (World of finance, 2025)
Introduction. One of the important global trends, alongside digitalization and technological transformation, sustainable development and environmental awareness, cybersecurity and data privacy, is urbanization, where certain cities create a dominant form of socio-economic organization, demonstrating higher productivity than individual countries. Urbanization and digitalization contribute to the development of the smart city concept, which more and more cities aspire to implement by developing smart innovations, smart infrastructure, and smart strategies. However, without thorough research, the creation of "smart cities" may lead to an exacerbation of digital divides and socio-economic inequality both between cities and within them, which is particularly evident during Ukraine's recovery in the wartime period.The purpose of the article of the research is to explore a range of issues related to identifying the barriers and opportunities within the environment, as well as to develop potential pathways for implementing strategic management in the urban development of Ukrainian cities in the post-war period based on the concept of a smart city.Results. The article analyzes definitions and explores current trends in the implementation of the smart city concept in Ukraine during the post-war period, particularly in the context of sustainable urban development, with a special focus on existing megatrends related to the spread of digital technologies in urbanization processes. It examines the main charac- teristics and functions of smart infrastructure, as well as the obstacles that may arise in its development. The potential benefits and challenges of implementing smart technologies in the reconstruction of urban infrastructure are evaluated, especially in the context of Ukraine's post-war recovery.Conclusions. The concept of a smart city integrates technological and digital innovations with social needs, fostering sustainable, innovative, and economic development of urban areas. It promotes European integration and is aimed at improving the quality of life for residents, representing a promising scenario for Ukraine. Strategic management of the development of smart cities in Ukraine requires a comprehensive approach that integrates digital technologies for managing urban processes, taking into account the specific risks, the needs of local communities, and the opportunities to enhance quality of life and achieve sustainable development goals, utilizing various methods and tools to improve the effectiveness of these processes. Key areas for urban development within this concept include safety, infrastructure, mobility, healthy living, information, and ecology.Prospects. Further scientific research should be directed towards studying the role of smart technologies in the development of smart city infrastructure and their impact on the quality of life for citizens; investigating ecological sustainability, including the implementation of “green” technologies and energy efficiency; analyzing mechanisms to ensure inclusivity and accessibility of services for all segments of the population; as well as exploring the role of participation and mechanisms for engaging the public in the planning and management processes of smart cities.